A Case of Chronic Neutrophilic Leukemia Incidentally Detected by (18)F-FDG PET/CT - Cheon, Miju (Diagnostics (Basel), 2021)
Chronic neutrophilic leukemia (CNL) is a rare, potentially aggressive, myeloproliferative neoplasm. To the best of our knowledge, there are no previous reports dealing with (18)F-FDG PET findings in CNL. We describe a case of CNL in a 69-year-old male, imaged with (18)F-FDG PET/CT at diagnosis and during treatment.